Identitas Perempuan dalam Budaya Patriarkis: Sebuah Kajian tentang Feminisme Eksistensialis Nawal el Sa'adawi dalam Novel “Perempuan di Titik Nol” - Pranowo, Yogie (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
Women in patriarchal cultures have been treated unjustly. They are looked upon as second-class beings and even repeatedly not considered a whole human being. Their presence is regarded as something incidental and not essential. For this reason the article wants to put forward and to explore Nawal el Sa'adawi's ideas in her novel Woman at Point Zero. The novel portrays the struggle of a woman in a life full of oppressions by the patriarchal system and culture. Firdaus, the main character in the novel, is a picture of the lives of women who continue to serve as the number two beings in a patriarchal culture. In this article, the author uses feminist existentialist Simone de Beauvoir's point of view to analyze the novel. It appears that both Beauvoir and Sa'adawi have echoed some strategies towards a full freedom for women to be fully acknowledged of their existence and they provided further suggestions for women to be aware of their own capabilities as a whole human being and to be brave without being overshadowed by male superiority.